The Role of Rimbun Conservation Village in Encouraging Nature Conservation and Improving Environmental Image - Setiawan, Ozi; Ramdani, Doni (JELAJAH: Journal of Tourism and Hospitality, 2024)
Rimbun Conservation Village has the potential as a model for sustainable ecotourism development amid global environmental challenges. This research aims to explore the effectiveness of Rimbun Conservation Village's role in environmental preservation and ecological image enhancement through ecotourism activities. The method used in this research utilizes qualitative methods, which include interviews, direct observation, and documentation. The results showed that Rimbun Conservation Village succeeded in raising community and tourist awareness of the importance of conservation, although there are some aspects that need to be improved, such as cleanliness, adequate facilities and accessibility. In addition, the participation of the community and tourists in activities such as tree planting and educational programs proved to provide economic benefits and increase tourist engagement. The main conclusion of this study is that Rimbun Conservation Village not only serves as a recreational center, but also as a living example of the harmonization between nature conservation and economic growth. To attract more tourists, it is recommended that the manager improve facilities and implement more effective digital marketing strategies. This research is expected to contribute to the development of ecotourism in other more sustainable tourist destinations in Indonesia.